Assessment of Bacillus thuringiensis and emamectin benzoate on the fall armyworm Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) severity on maize under farmers’ fields in Ghana - Koffi, D.; Kyerematen, R.; Osae, M.; Amouzou, K.; Eziah, V.Y. (Springer, 2021)
The introduction of fall armyworm (FAW), Spodoptera frugiperda (Lepidoptera: Noctuidae) into Ghana is a threat to maize production. This study determined the severity of this pest on maize production subjected to Bacillus thuringiensis (Bt), emamectin benzoate (Eb) sprayed and unsprayed farms under farmers’ practices in Ghana. At least one farm per treatment was selected in each Agro-Ecological Zone (AEZ) for data collection throughout the maize phenology during three production seasons. Percent damaged plants and ears were determined, the proportion of feeding damage on leaves and ears was scored, and yields measured on each farm. Ear damage was most severe in the Guinea Savannah Agroecological Zone with a correspondingly lower yield. The highest yield was recorded from the Tropical Rain Forest zone. The damage levels decreased when plants aged, but the scoring of damage level on attacked ears was greater than that on leaves. Maize plant damage was highest with corresponding lowest yields on unsprayed farms compared to sprayed farms which recorded similar results for both insecticides. Bt and Eb based insecticides (applied at 50g/15L H2O/ha and 75mL H2O/ha, respectively) are efective on FAW larvae and are therefore recommended for FAW management in Ghana.
Research Article
Keywords: Fall armyworm; Incidence; Severity; Seasons; Maize phenology; Management